Effects of aspirin on stroke and mortality in tubercular meningitis: a meta-analysis of randomized controlled trials - Li, Fang; Zhou, Yi; Tan, Jingsi; Meng, Zifei; Wang, Laifa; Zhu, Lemei (Frontiers in Medicine, 2025)
BackgroundTubercular meningitis (TBM) remains a highly lethal form of extrapulmonary tuberculosis. Aspirin, owing to its anti-inflammatory and antithrombotic properties, has been explored as adjunctive therapy, but its clinical benefits remain controversial. This meta-analysis aimed to evaluate the efficacy and safety of adjunctive aspirin in TBM, particularly its impact on stroke and all-cause mortality, and to explore the influence of different aspirin dosages.MethodsWe systematically searched four databases for randomized controlled trials (RCTs) comparing adjunctive aspirin versus standard anti-tuberculosis therapy (ATT) in TBM patients. Outcomes included stroke, all-cause mortality, and bleeding events. Random-effects meta-analyses were conducted to pool risk ratios (RRs) with 95% confidence intervals (CIs). A network meta-analysis (NMA) was performed to assess the effect of different aspirin doses. The quality of evidence was assessed using the GRADE framework.ResultsFive RCTs involving 580 participants were included. Adjunctive aspirin significantly reduced the risk of stroke (RR: 0.56; 95% CI: 0.33–0.95), with low-dose aspirin showing superior protective effect compared to high-dose in NMA. However, aspirin did not reduce all-cause mortality (RR: 1.00; 95% CI: 0.65–1.55) or increase bleeding risk. Sensitivity analysis indicated limited robustness of stroke outcomes, and overall evidence quality ranged from low to very low.ConclusionAdjunctive low-dose aspirin may reduce the risk of stroke in TBM without increasing bleeding events, although it has no clear effect on mortality. Further high-quality trials are needed to confirm the optimal dosing strategy and long-term benefits of aspirin in TBM management.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251110022, identifier CRD420251110022.